A Critical Analysis of the Three Conditions of Knowledge - Ogaba, Isenyo Solomon (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
In analyzing the three different conditions of knowledge, in this work, we find that Truth as a necessary condition of knowledge ultimately amounts to a minimal conception of truth. That is if S knows that p is true, then, p is true. Secondly, we find that Belief as a necessary condition of knowledge is not used in a metaphoric sense of ‘belief’. Also, that it neither entertains the performative sense of knowledge nor does it allow us to interpret a guess as an instance of knowledge. Either of the two might lead to arguing for knowledge without belief. Belief is taken in such a sense that it necessarily follows from the knowledge and, accordingly, the condition can be stated as that if S knows that p, then, S believes that p. Third, this paper finds out that the main objective of keeping Justification as a necessary condition of knowledge is to distinguish knowledge from accidental true beliefs. Every instance of knowledge necessarily satisfies that the subject has enough evidence to be justified in what he/she believes to be true. In other words, if S knows that p, then, S is justified in believing that p. Also, in this work, I explained that there is no satisfactory answer to Gettier’s problem, hence, there is no necessity of identifying knowledge with Justified True Belief.